2015
DOI: 10.3402/meo.v20.25923
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of gender-based discrimination during surgical training and practice

Abstract: BackgroundWomen represent 15% of practicing general surgeons. Gender-based discrimination has been implicated as discouraging women from surgery. We sought to determine women's perceptions of gender-based discrimination in the surgical training and working environment.MethodsFollowing IRB approval, we fielded a pilot survey measuring perceptions and impact of gender-based discrimination in medical school, residency training, and surgical practice. It was sent electronically to 1,065 individual members of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
196
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(216 citation statements)
references
References 32 publications
18
196
1
1
Order By: Relevance
“…De igual forma, el sexo no se relacionó con un mayor efecto sobre el puntaje global del síndrome de desgaste profesional y el de sus subescalas. Aunque se reconoce que la cirugía es una profesión 'masculina' y que puede existir una tendencia según el sexo en la formación que puede favorecer el desgaste en la mujeres 17,18 , los resultados de este estudio descartaron esta asociación, en particular, si se considera que el 28 % de la población evaluada era del sexo femenino. Finalmente, las posibles asociaciones entre la gravedad del síndrome de desgaste profesional y el carácter privado o público de los programas, en razón de los aspectos socioeconómicos, fueron descartadas en este estudio.…”
Section: Discussionunclassified
“…De igual forma, el sexo no se relacionó con un mayor efecto sobre el puntaje global del síndrome de desgaste profesional y el de sus subescalas. Aunque se reconoce que la cirugía es una profesión 'masculina' y que puede existir una tendencia según el sexo en la formación que puede favorecer el desgaste en la mujeres 17,18 , los resultados de este estudio descartaron esta asociación, en particular, si se considera que el 28 % de la población evaluada era del sexo femenino. Finalmente, las posibles asociaciones entre la gravedad del síndrome de desgaste profesional y el carácter privado o público de los programas, en razón de los aspectos socioeconómicos, fueron descartadas en este estudio.…”
Section: Discussionunclassified
“…If female students do not see themselves as surgeons because they do not have opportunities to observe female surgeons, they cannot see for themselves that it might be possible to combine family life with such a career. Bruce et al () found that “Despite the strides that have been made in gender equality over the past century, more than half of our respondents reported experienced or observed gender‐based discrimination.” They also reported that “within the male‐dominated world of surgery, where women are represented by low numbers, women discriminating against women may perpetuate the cycle of gender disparity. It has been proposed that there is a dynamic between the female nurses' nurturing characteristics, which are traditionally feminine, and the female surgeons' fight to attain agency as a leader, often requiring calculated cooperation in the workplace.” Furthermore, they noted that because “mentorship and early exposure play a positive role in women's decisions to enter surgery” they believe that “a greater proportion of successful women in surgical departments should allow more female students to recognize surgery as a viable option.” In their systematic literature review of databases relating to gender differences in surgical education at an undergraduate level, Burgos and Josephson () conclude that there is “an underrepresentation of women in surgical academia, due to lack of role models and gender awareness.”…”
Section: Recommendationsmentioning
confidence: 90%
“…Sanfey et al demonstrated that generation and gender are both important influences on career choices [16]. Male surgeons are just as likely as female surgeons to report that quality of life dissuades them from choosing surgery; in fact, surgical workload and family concerns appear to be less of a deterrent for women surgeons [7,8,17]. In our study, 26 % of the female surgeons have children and 64 % wish to have children in the future.…”
Section: Discussionmentioning
confidence: 44%
“…Respondents reported that job satisfaction and career advancement were the areas most affected by gender-based discrimination. As a result, 24 % left and 45 % considered leaving a position during training or practice [7]. With regard to career preparation or structural barriers, no differences were observed between male and female surgeons.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation